2010
DOI: 10.1001/archinternmed.2010.39
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Disclosing Financial Ties in Research and Clinical Care

Abstract: Patients believe that FTs influence professional behavior and should be disclosed. Patients, physicians, and research participants believe FTs decrease the quality of research evidence, and, for some, knowledge of FTs would affect willingness to participate in research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
77
1
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(81 citation statements)
references
References 47 publications
2
77
1
1
Order By: Relevance
“…Although orthopaedic surgeons maintain strong ties with device manufacturers owing to the need for physician input in the development of new and innovative surgical devices, previous analyses of the Sunshine act data revealed a large difference between the field and others. While previous research has shown that industry payments may affect provider practices [3,4,10,18,21,30,40] and patient perceptions of their physicians [32,48], our study showed that substantial disparities in payments do exist among orthopaedic surgeons and that the median orthopaedic surgeon does not receive a large sum. The majority of total payments to orthopaedic surgeons are for royalties and licenses for intellectual property, which actually foster device innovations and are viewed more positively by patients and physicians [8].…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…Although orthopaedic surgeons maintain strong ties with device manufacturers owing to the need for physician input in the development of new and innovative surgical devices, previous analyses of the Sunshine act data revealed a large difference between the field and others. While previous research has shown that industry payments may affect provider practices [3,4,10,18,21,30,40] and patient perceptions of their physicians [32,48], our study showed that substantial disparities in payments do exist among orthopaedic surgeons and that the median orthopaedic surgeon does not receive a large sum. The majority of total payments to orthopaedic surgeons are for royalties and licenses for intellectual property, which actually foster device innovations and are viewed more positively by patients and physicians [8].…”
Section: Discussioncontrasting
confidence: 74%
“…After royalties, the second largest category of payments made to orthopaedic surgeons was for consulting fees. As opposed to industry payments for food, travel, or gifts, which are viewed negatively by patients [8,32,41], patients mostly support physicians serving as industry consultants [29]. However, concerns remain for conflicts of interest in this type of financial relationship, and further study of the larger influence of industry consultants is needed [24].…”
Section: Discussionmentioning
confidence: 99%
“…Compelling arguments can be made that disclosure does not effectively prevent, help identify, or avoid the appearance of investigator bias [9]. Potential research subjects report a strong interest in disclosure of investigator conflicts [22,23]. As a way of achieving transparency disclosure might be expected to increase trust.…”
Section: Regulation Of the Individualmentioning
confidence: 99%
“…In addition to information on study funding, consumers of research, including patients and physicians, want researcher financial ties to industry to be disclosed 64 and consider authorindustry financial ties in assessing the quality of research evidence. [64][65][66] The authors of the PRISMA statement should also consider recommending that metaanalyses report author-industry financial ties disclosed in included RCTs or report that there was no disclosure statement.…”
Section: Commentmentioning
confidence: 99%
“…[64][65][66] The authors of the PRISMA statement should also consider recommending that metaanalyses report author-industry financial ties disclosed in included RCTs or report that there was no disclosure statement. Although author-industry ties are less frequently reported than study funding sources in published reports of RCTs included in meta-analyses, the proportion of RCTs reporting author-industry financial ties will likely increase with the recent introduction of ICMJE disclosure guidelines.…”
Section: Commentmentioning
confidence: 99%